Contacts of suicide attempters with GPs prior to the event: a comparison between Stockholm and Bern - Michel, K.; Runeson, B.; Valach, L.; Wasserman, D. (Acta psychiatrica Scandinavica, 1997)
The aim of this study was to investigate patterns of contact made with GPs by subjects in two cities prior to attempting suicide, in order to determine whether differences in the health care systems could be a possible factor influencing the help‐seeking behaviour of people experiencing suicidal crises. Structured interviews were conducted with suicide attempters from geographically defined catchment areas in two countries with private and national health care systems, respectively. The subjects were suicide attempters, admitted consecutively, aged ≥15 years and living either in Stockholm (n=202) or in Bern (n=66). Patients living in Bern had seen their GPs more regularly and more frequently throughout the year. There was an increase in the number of visits to the GP prior to the suicide attempt in both cities, but it was greater in Stockholm than in Bern. However, in Stockholm fewer patients who saw their GP in the week before the attempt talked about their suicidal thoughts. The differences in help‐seeking behaviour between the two patient samples may be related to the higher number of practising GPs and a more personal and consistent patient‐doctor relationship in Bern. It is possible that the private medical care system in Switzerland lowers the threshold enabling patients to talk to their GP about their suicidal plans. The results suggest that in both cities there is scope for improving communication of the suicidal patient with his or her doctor.